Development through Empowerment: Delivering Effective Public Services - A Literature Review - Guo Xu (Asian Development Bank (ADB), 2013)
This paper reviews the channels through which empowerment may improve the efficiency and quality of public service delivery, particularly in developing Asia. Departing from a macro perspective, we focus and revisit microeconomic evidence for three broad measures aimed at empowering the poor: empowerment through voice, empowerment through exit, and empowerment through information.
hdl:11540/4228
Keywords: H40; Y30; 330; empowerment; public service delivery; accountability